Sustainability energy policy reform in Malaysia - Ahmad Ludin, Norasikin; Han, Phoumin; Mohd Chachuli, Fairuz Suzana; Hamid, Norul Hisham (Springer, 2022)
The global energy system must be reformed. Energy supply systems largely based on fossil fuels must be replaced with those based on renewable energy (RE) to achieve at least 66% in limiting global temperature increase to below 2° C in the present century. The world remains below the 2° C climate objective and is even farther from attaining the aspirational target of limiting global warming to 1.5° C. Energy efficiency (EE) and RE are the pillars of the energy transition. They can provide more than 90% of the required energy-related CO2 emission reduction by using safe, reliable, affordable, and widely available technologies. Similarly, Malaysia is also transforming fossil-based energy into sustainable energy, such as RE. Malaysia is endowed with abundant resources. Solar, hydropower, and biomass are amongst the most popular sustainable energy forms available in Malaysia. Therefore, beginning sustainable energy growth for the current and future generations without policy intervention is critical for the country. This chapter aims to provide the readers with an overview of Malaysia’s commitment to facilitate sustainable energy policy reforms. It discusses RE development, including the key focus areas, policies, achievements, targets, existing initiatives that the government and the private sector are undertaking, and upcoming initiatives wherein relevant government entities are committed to fulfilling their roles. A study on policy performance and transition is also conducted using data envelopment analysis. The study identifies the effects of policy implementation on RE growth and the policy landscape in Malaysia. This chapter also highlights the roles of energy policy reform players and existing barriers. Finally, it concludes that some lessons learned from Malaysia’s experience in driving sustainable energy policy reforms may be critical if the projected development is realised without incurring substantial economic, social, and environmental consequences.